Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1051/limn/2017025
|View full text |Cite
|
Sign up to set email alerts
|

Benthic diatom communities in high altitude lakes: a large scale study in the French Alps

Abstract: -Altitude lakes are weakly impacted by human activities. This makes them choice ecosystems to understand how biological communities are impacted by natural factors. This question was addressed to littoral benthic diatoms, a largely used ecological indicator. We wanted to know if benthic diatoms in lakes are more impacted by local varying factors (altitude, lake depth...) or regional varying factors (geology). The study area takes place in the Northern French Alps. Littoral benthic diatoms of 63 natural lakes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 62 publications
(70 reference statements)
4
22
0
Order By: Relevance
“…Because HCO 3 − concentrations and spatial variables partly mirror vegetational changes across the sampled ecotone, we assume that additional environmental variables, such as vegetation type or related environmental variables that have not been exclusively considered in this study, contribute to the diatom community assembly. Geographic distance, however, seems to be of weaker influence, this has been shown in other alpine and boreal studies (Feret, Bouchez, & Rimet, ; Teittinen & Soininen, ) and has been demonstrated for the genus Staurosira across a similar area (Stoof‐Leichsenring et al, ) and for this study as well.…”
Section: Discussionsupporting
confidence: 76%
“…Because HCO 3 − concentrations and spatial variables partly mirror vegetational changes across the sampled ecotone, we assume that additional environmental variables, such as vegetation type or related environmental variables that have not been exclusively considered in this study, contribute to the diatom community assembly. Geographic distance, however, seems to be of weaker influence, this has been shown in other alpine and boreal studies (Feret, Bouchez, & Rimet, ; Teittinen & Soininen, ) and has been demonstrated for the genus Staurosira across a similar area (Stoof‐Leichsenring et al, ) and for this study as well.…”
Section: Discussionsupporting
confidence: 76%
“…Alpha and beta diversity estimates based on morphological investigations have a negative correlation with water depth. A decreasing richness related to increasing water depth has been found in other morphologically based diatom studies: for example, within-lake analysis of water-depth variations in Canadian Worth Lake [67], within Lugu Lake, China [68], in Lake Ohrid in Southern Europe [11] and across a spatial dataset of alpine lakes with varying water depth [69]. In general, variations in water depth are related to differences in substrate [70] and correlate with water turbulence [71].…”
Section: Relationship Between Lake Water Depth and Genetic And Morphosupporting
confidence: 52%
“…Encyonopsis subminuta is regarded as a cosmopolitan taxon, occurring in the temperate and boreal zone. It is most abundant in oligo-to mesotrophic waters with electrolytic conductivity between 190-250 µS cm -1 (Krammer 1997;Noga et al 2014;Novais et al 2014;Feret, Bouchez & Rimet 2017). Encyonopsis subminuta may be sensitive to the concentration of Fe ions; however, the increase of these ions is associated with a drop in pH.…”
Section: Encyonopsis Subminuta (Esum) (Figs 5 Bbb-ggg)mentioning
confidence: 99%